Green Finance Based Access to Financing in Islamic Microfinance: A Case Study of the UMi AMBO Program in Padang - Seppi Mustion; Aulia Ikhwani; Natasya Amelia Wulandari; Hulwati; Ahmad Wira (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
This study aims to analyze access to financing based on green finance, using a case study of the UMi AMBO program. The research employs a qualitative approach, collecting data through interviews, observations, and documentation. The implementation of green finance program in Padang not only enhances access to financing for micro enterprises but also encourages environmentally friendly business practices. This requires simplification of procedures, improvement in banking service quality, and strengthening of the capacity of micro, small, and medium enterprises. The UMi AMBO financing program has proven effective in supporting microenterprise development and promoting financial inclusion for small business actors. Innovations in the application of green finance-based financing and enhancement of mentoring programs for beneficiaries are necessary. If managed properly, the ultra micro financing can serve as a model for other financial institutions to implement green finance, eliminate predatory lending practices, and empower MSMEs to grow sustainably. It can be concluded that the program is also based on the principles of Islamic economics, such as ‘adl), balance (tawazun), prohibition of usury (riba), social responsibility (maslahah), and profit-and-loss sharing mechanisms. These principles ensure that financing is conducted ethically and sustainably, in alignment with Islamic values and the goals of sustainable economic development.